Productivity of Arrowroots and Taro Grown Under Superior Teak Clones with Several Levels of Stand Density - Prehaten, Daryono; Hardiwinoto, Suryo; Naâ€™iem, Mohammad; Supriyo, Haryono; Widiyatno, Widiyatno; Rodiana, Dian (Biosaintifika: Journal of Biology & Biology Education, 2021)
Perum Perhutani has an important role in providing food and wood for people. Diversity and diversification of food will reduce the need for one type of food, namely rice as a staple food. Some tuber and rhizome are source of alternative foodstuffs, such as taro and arrowroot. This study aimed to determine the suitability and productivity of arrowroot and taro planted under old superior teak clones with several levels of stand density. Arrowroot and taro were planted under 14-year-old teak stands with 4 levels of density. Both plants were planted in the form of an array, measuring of 3m x 15m, with a spacing of 75cm x 75cm between plants. They were arranged in Randomized Completely with Block Design (RCBD) placed in 4 blocks of observation as replications.Â  The results showed that under superior teak clone had the potential to be planted with arrowroot and taro. Teak stand density influenced significantly some characteristics of arrowroot (leaves number, leaves area, stem height, stem diameter, root length) and taro (stem diameter, tuber diameter). Arrowroot productivity per hectare increased with low density of teak stands, accounted for 55, 59, 80, and 88 kg respectively. Meanwhile, taro productivity from very high to low teak density were 365, 301, 523, and 426 kg/ha. The novelty of this study is that there is no record of intercropping studies on old superior teak clones, so this is among the first studies. The benefit of from this research result, it could be employed by Perhutani to support the Indonesian government in the national food security program